Caffeic acid phenethyl ester protects against oxidative stress-related renal dysfunction in rats treated with cyclosporin A - Wongmekiat O. (2014)
The therapeutic index of cyclosporin A (CsA), an immunosuppressive drug, is limited by its nephrotoxic effect. Oxidative stress is suggested to play a crucial role as pathogenic factors. The present study aimed at investigating the effects of caffeic acid phenethyl ester (CAPE), a phenolic antioxidant, on renal function, morphology, and oxidative stress following CsA treatment. Rats were treated with vehicle, CsA (50mg/kg), and CsA plus CAPE (10 and 30μmol/kg) for 10days. Renal function, histopathology, and tissue malondialdehyde (MDA) and reduced glutathione (GSH) levels were evaluated 24h after the last treatment. CsA produced nephrotoxicity as indicated by a significant increase in serum creatinine and blood urea nitrogen, but decrease creatinine and urea clearance compared to those treated with vehicle. Severe vacuolations and tubular necrosis were evident in the kidney of CsA-treated rats. CsA also increased renal MDA and decreased GSH content significantly. Administration of CAPE along with CsA restored all the changes caused by CsA. These results clearly demonstrate the pivotal role of oxidative stress and its relation to renal dysfunction and also point to the protective potential of CAPE against CsA nephrotoxicity. The protection afforded by CAPE is mediated, at least in part, through inhibiting renal lipid peroxidation and enhancing or maintaining the antioxidant glutathione content. © 2010 The Authors Fundamental and Clinical Pharmacology © 2010 Société Française de Pharmacologie et de Thérapeutique.